2017
DOI: 10.5530/ijper.51.3.70
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Hydro-Ethanolic Extract of Pothos scandens L on key Carbohydrate Metabolizing Enzymes and Xenobiotic Marker Enzymes in DMBA Induced Experimental Mammary Carcinoma

Abstract: Objective: In the present study, phytochemical evaluation and the therapeutic effect of 50 % hydro-ethanolic extract of aerial parts of Pothos scandens (HEEPS) on glycolytic enzymes, TCA cycle enzymes, gluconeogenic enzymes and xenobiotic marker enzymes in the liver and breast tissues of 7, 12 -Dimethylbenz [a] anthracene (DMBA) induced breast cancer bearing rats were carried out. Materials and Methods: Five groups of (each group six rats) female albino Spargue-Dawley rats were taken. Group I (control), Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
1
0
1
Order By: Relevance
“…36 In a study by Jethinlalkhosh et al reported the therapeutic effect of P. scandens on carbohydrate metabolizing enzymes, suggesting the species P. scandens as potential anticancer activity. 21…”
Section: Anticancer Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…36 In a study by Jethinlalkhosh et al reported the therapeutic effect of P. scandens on carbohydrate metabolizing enzymes, suggesting the species P. scandens as potential anticancer activity. 21…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Fig.-4: Structures of Flavonoids(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) …”
unclassified